Graphene and Two-Dimensional Materials-Based Flexible Electronics for Wearable Biomedical Sensors - Joe, Daniel J. J.; Park, Eunpyo; Kim, Dong Hyun; Doh, Il; Song, Hyun-Cheol; Kwak, Joon Young (MDPI AG, 2023)
The use of graphene and two-dimensional materials for industrial, scientific, and medical applications has recently received an enormous amount of attention due to their exceptional physicochemical properties. There have been numerous efforts to incorporate these two-dimensional materials into advanced flexible electronics, especially aimed for wearable biomedical applications. Here, recent advances in two-dimensional materials-based flexible electronic sensors for wearable biomedical applications with regard to both materials and devices are presented.